Courting sanctity : holy women and the Capetians - Field, Sean L. (Sean Linscott), 1970- (Cornell University Press, 2019)
"Courting Sanctity argues that during the reign of Louis IX (r. 1226-70) holy women were central to the rise of the French royal family's self-presentation as uniquely favored by God, that their influence began to be questioned at the court of Philip III (r. 1270-85), and that would-be holy women were increasingly assumed to pose physical, spiritual, and political threats by the death of Philip IV (r. 1285-1314)"--